THE EFFECT OF STRATEGIC PHYSIOGNOMY IN ACHIEVING ORGANIZATIONAL INGENUITY, AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF WORKERS IN THE TOURISM AUTHORITY) (World Bulletin of Management and Law, 2022)
The current study aims to clarify the role strategic physiognomy(SA) plays in achieving organizational ingenuity (OI) , resulting intellectual cases as a result of interaction of strategic innate variables represented by its dimensions (inspiration, empowerment, deep understanding(DU), (OA) represented by dimensions (after exploiting opportunities, after exploring opportunities) , that Because of their impact on the ideas , style of the managers by directing them in managing , organization, and the study was applied to , directors, heads of departments , people’s officials in the Iraqi Tourism Authority(ITA), who numbered (35), data was collected by means of a questionnaire. Arithmetic, standard deviation, relative importance, multiple regression, across a set of statistical programs represented in (Amos, spss) , one of most prominent conclusions that have been reached is existence of a correlation , impact relationship between strategic intuition and organizational ingenuity(OI).
Keywords: strategic physiognomy; organizational Ambidexterity